The Corporate Mystic: Mengintegrasikan Nilai-Nilai Spiritual dalam Manajemen Modern untuk Meningkatkan Efektivitas Kepemimpinan dan Keberlanjutan Organisasi - Imama Zuchroh; Muniroh (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study explores how spiritual values can be authentically integrated into modern management to enhance leadership effectiveness and organizational sustainability. Employing a qualitative multi-method approach that includes comparative case studies and document analysis of leading corporations such as Patagonia, Unilever, and Mindvalley, the research identifies key practices of spiritually grounded leadership. Findings reveal that value-driven organizations consistently report higher employee engagement, innovation, and well-being, as confirmed by data from the World Economic Forum (2023), Deloitte (2024), and the International Labour Organization (2023). Spiritual leadership anchored in integrity, compassion, and interconnectedness emerges as a measurable determinant of organizational performance, not a philosophical abstraction. The study concludes that authentic spiritual integration fosters ethical governance, trust, and sustainable productivity. It proposes a conceptual framework positioning the “corporate mystic” as a leader who aligns consciousness with strategy, enabling organizations to harmonize profitability with purpose. This integration of humanistic and managerial excellence signifies a transformative evolution in global leadership paradigms.